Resumos do III Modelo Diplomático da Fundação Osorio FOMUN 2023 - Giorno, Leonardo; Palhares, José Vítor; Machado, Rafaela; Scorza, Joana; Tarcitano, Lucas; Azevedo, Nicole; Gama, Giulia; da Hora, Brenda; de Araújo, Tainá; Nascimento, Maria Angélica; Brito, Suellen de Sant’Anna; Santos, Luana da Hora; et al. (Revista Científica Fundação Osorio, 2023)
Não possui resumo.